(untitled) (Research, Society and Development, 2021)
This article aims to map studies on educational actions about patient safety in the perioperative period, during hospitalization. It is a narrative review based on the mapping of nurses productions, in Brasilian theses and dissertations. Five searches were carried out on december 15, 2020 in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel, with varying combinations of descriptors and/or keywords: patient, surgical, patient education as a subject, education in health, patient safety, nursing, perioperative nursing, preoperative period, postoperative period, hospital. The boolean operator “AND” was used to interconnect search terms. Nine productions were selected and analyzed. Several positive perceptions of patients were identified regarding the educational sctions developed, valuing information on hospitalization, surgeries and the quality of various topics addressed for patient safety. The research made it possible to learn about studies that focus on educational actions about patient safety in the perioperative period developed during hospitalization, but they do not make in clear whether patients relate educational actions in health to safety. The analysis of the studies that integrated this review demonstrates the lack of investigations that include educational actions by nurses aimed at the safety of surgical patients.